Crosstalk between cytotoxic CD8+ T cells and stressed cardiomyocytes triggers development of interstitial cardiac fibrosis in hypertensive mouse hearts - Brassington, Kurt; Kanellakis, Peter; Cao, Anh; Toh, Ban-Hock; Peter, Karlheinz; Bobik, Alex; Kyaw, Tin (Frontiers in Immunology, 2022)
Graphical Abstract Cardiac fibrosis developed from fibrotic remodelling due to hypertension leads to heart failure. Immune cells are abundantly accumulated in fibrotic regions, but exact mechanisms how they contributed to cardiac fibrosis are not clear. Here we demonstrated that CD8 T cells are major contributor to cardiac fibrosis in hypertensive hearts. Stressed cardiomyocytes express STING-dependent RAE-1 that activates NKG2D + CD8 T cells to induce apoptosis of stressed cardiomyocytes. Preventing STING signalling in stressed cardiomyocytes attenuates cardiac fibrosis. Pharmacologically inhibiting cardiomyocayte-RAE-1 and CD8+ T cell-NKG2D axis may be a potential therapeutic strategy to prevent cardiac fibrosis in HFpEF patients.